Power Spectral Changes of Quantitative EEG in the Subjective Cognitive Decline: Comparison of Community Normal Control Groups - Jeong HT (Dove Medical Press, 2021)
Ho Tae Jeong,1 Young Chul Youn,1 Hyun-Ho Sung,2 Sang Yun Kim3 1Department of Neurology, Chung-Ang University of College of Medicine, Seoul, Korea; 2Department of Clinical Laboratory Science, Dongnam Health University, Suwon, Korea; 3Department of Neurology, Seoul National University Bundang Hospital, Seoul National University College of Medicine, Seongnam, KoreaCorrespondence: Young Chul YounDepartment of Neurology, Chung-Ang University College of Medicine, 102, Heukseok-ro, Dongjak-gu, Seoul, 06973, KoreaTel +82 2 6299 1485Fax +82 2 6299 1493Email neudoc@cau.ac.krPurpose: The purpose of this study is to compare and analyze the power spectral changes between subjective cognitive decline (SCD) subjects and normal controls (NC) while checking the preclinical stage of AD in the SCD subjects and to use the derived data for biomarker research that can diagnose early-stage AD in the future.Methods: We recruited 23 SCD patients and 23 normal control subjects and QEEG analysis including power spectral density (PSD) and source-level analysis were performed. An automated preprocessing procedure and statistical analysis were performed by iSync Brain® (iMediSync Inc., Republic of Korea) (https://isyncbrain.com/) using the international standard 10– 20 system (19 electrodes).Results: Absolute PSD, there was no statistically significant difference in all of the EEG power measurements of the 19 channels. In the relative PSD analysis, the average delta band power of the SCD group was significantly higher in Fp2, F4, and F8 than NC. Alpha1 band power of the O1 channel was 22.56± 16.05 for the SCD group and 33.19± 19.05 for the NC (p-value < 0.05). Source-level analysis did not show a statistically significant difference.Conclusion: SCD subjects showed a partial increase of delta waves in the frontal lobe region and a partial decrease in alpha1, a fast wave in the occipital region, compared to the NC. SCD is considered one of the earliest clinical symptoms of AD and it is predicted to be related to minor nerve damage. We were able to observe the power spectral changes in SCD subjects in this cross-sectional study, a large number of subjects and longitudinal studies are needed to evaluate their predictability for future deterioration such as conversion to MCI.Keywords: Alzheimer, cognitive impairment, dementia, hypertension